KEBIJAKAN DIVIDEN, DEWAN KOMISARIS INDEPENDEN TERHADAP KINERJA KEUANGAN - Dwi Lestari, Anggun; Putri Suryati, Intan; Rahma, Dwi; Febri Rinjani, Dela (Universitas Muhammadiyah Bengkulu, 2025)
The Purpose Of This Study Is To Determine The Influence Of The Dividend Policy And The Independent Board Of Commissioners On Financial Performance In Manufacturing Companies In The Food And Beverage Sub-Sector Listed On The Indonesia Stock Exchange For The Period 2020 – 2023. The Population In This Study Is All Manufacturing Companies In The Food And Beverage Sub-Sector Listed On The Indonesia Stock Exchange For The 2020-2023 Period. The Method Used In This Study Is A Quantitative Method. The Sample Used In This Study Is 16 Companies. In This Study, The Data Analysis Method Uses Multiple Linear Regression Analysis Using IBM SPSS 26. Based on the results of data analysis, it is concluded that dividend policy has a negative effect on financial performance. the board of commissioners has a positive effect on financial performance. The Results Of This Study Show That Dividend Policies And Independent Boards Of Commissioners Have An Effect On Financial Performance. Keywords: Dividend Policy, Independent Board Of Commissioners, Financial Performance